A case of rare pulmonary sequestration complicated with congenital heart disease treated by arterial embolization and atrial defect closure: A case report and review of literature - Tang, Mi; Wu, Xun; Hu, Shijun; Wu, Qin; Yang, Danni; Iroegbu, Chukwuemeka Daniel; Fan, Chengming; Yang, Jinfu (Frontiers in Cardiovascular Medicine, 2022)
Pulmonary sequestration with congenital heart disease is a rare congenital malformation. Herein, we report a 19-month-old toddler diagnosed with right lower pulmonary sequestration, right pulmonary artery dysplasia, right lower pulmonary venous ectopic drainage, and a right-sided heart with an atrial septal defect. The pulmonary sequestration had a rare blood supply, such as confluent arteries with the renal vessels draining into the hepatic veins. Arterial embolization and atrial defect closure were used to treat the rare congenital malformation with satisfactory results.